2021
DOI: 10.3171/2021.5.focus20813
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality navigation for cranial biopsy and external ventricular drain insertion

Abstract: OBJECTIVE The aim of this study was to evaluate the accuracy (deviation from the target or intended path) and efficacy (insertion time) of an augmented reality surgical navigation (ARSN) system for insertion of biopsy needles and external ventricular drains (EVDs), two common neurosurgical procedures that require high precision. METHODS The hybrid operating room–based ARSN system, comprising a robotic C-arm with intraoperative cone-beam CT (CBCT) and integrated video tracking of the patient and instruments u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…The final prototype was assessed by experienced neurosurgeons, who found the head phantom to meet the expectations of both anatomical and surgical realism. A detailed quantitative assessment of the model with respect to the simulated surgical outcomes has been reported in a previous study [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final prototype was assessed by experienced neurosurgeons, who found the head phantom to meet the expectations of both anatomical and surgical realism. A detailed quantitative assessment of the model with respect to the simulated surgical outcomes has been reported in a previous study [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…To achieve authenticity and maintain low costs, the materials used for production were carefully selected, and tested in different concentrations and compositions to match criteria formulated from published data. In addition, the model was tested and evaluated by neurosurgeons for representativity and utility [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phantom studies and cadaver simulations have also demonstrated promising applications of AR in cranial neurosurgery with techniques for cranial biopsy or accurate catheter placement. This raises the potential for very precise minimally invasive procedures, which could perspectively be applied bedside with minor efforts [ 33 , 36 ]. AR-assisted puncture of the gasserian ganglion for precise radiofrequency ablation in trigeminal neuralgia provides another interesting approach in minimally invasive interventional pain management [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for intraoperative use, descriptions of AR-guided navigation can be found primarily for endoscopic procedures, including endoscopic transsphenoidal skull base surgery [ 9 , 25 , 29 ]. Several phantom studies also demonstrate potential applications for cranial biopsy or catheter placement [ 33 , 36 ].…”
Section: Introductionmentioning
confidence: 99%